A new optical sensing technique for monitoring shear of rock bolts. (June 2017) - Forbes, Bradley; Vlachopoulos, Nicholas; Hyett, Andrew J.; Diederichs, Mark S.
Highlights: An instrumented approach to measure the strain profile of rock bolts is presented. A solution is derived for the 3D determination of strain and displacement. The solution is demonstrated through a series of laboratory experiments. Abstract: In addressing limitations of conventional ground support measurement, a novel optical strain sensing technique is presented that is capable of measuring strain at increments as low as 0.65 mm along the entirety of an optical sensor affixed to a support element. The technique considers monitoring three sensing lengths along the profile of a fully grouted rock bolt element using a single optical fiber, which, in turn, allows the derivation of both the principle strain and principle strain direction along the bolt. A series of three experiments, which include: symmetric bending, combined axial load and bending, and double shear loading are presented and highlight the potential of the technique to capture bolt behaviour under such generalized rock bolt loading conditions. Analogized as a distributed strain rosette, the optical technique can distinguish both the coaxial and bending induced constituents of the total strain in the bolt regardless of load orientation.